2009
DOI: 10.1159/000214844
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Agonist Reduces Aromatase Cytochrome P450 and Cyclooxygenase-2 in Ovarian Endometrioma and Eutopic Endometrium of Patients with Endometriosis

Abstract: Aims: To investigate whether the GnRH agonist may reduce aromatase P450 and COX-2 in the eutopic endometrium of patients with endometriosis and ovarian endometrioma. Materials and Methods: Endometrial specimens and ovarian endometrioma were obtained from 15 women with endometriosis undergoing laparoscopic surgery. The stromal cells of the eutopic endometrium and ovarian endometroma were cultured in the presence of the GnRH agonist (leuprolide acetate 0, 1, 5 and 10 μM) for 24 h. To investigate the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
2
14
0
1
Order By: Relevance
“…However, our findings and those of Surrey et al (13) parallel the observations that ovarian suppression with either GnRH agonist (11) or OC (12) corrects the endometrial alterations seen in endometriosis. This therefore suggests that GnRH agonist or OC treatment may improve ART outcomes in endometriosis through an endometrial effect.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…However, our findings and those of Surrey et al (13) parallel the observations that ovarian suppression with either GnRH agonist (11) or OC (12) corrects the endometrial alterations seen in endometriosis. This therefore suggests that GnRH agonist or OC treatment may improve ART outcomes in endometriosis through an endometrial effect.…”
supporting
confidence: 90%
“…Moreover, there is also mounting evidence that an overt resistance to progesterone occurs in endometriosis (9), as seen in labor (10). These endometrial anomalies, both morphologic and functional, can be temporarily corrected by suppressing ovarian function with the use of gonadotropin-releasing hormone (GnRH) agonists (11) or oral contraceptives (OC) (12).…”
mentioning
confidence: 99%
“…In this respect it is noteworthy that aromatase cytochrome P450, the enzyme that catalyses the conversion of androgens to oestrogens, is overexpressed in women with endometriosis and adenomyosis, and that therapy with GnRHa decreases expression of aromatase cytochrome P450 in the eutopic endometrium of women with adenomyosis and endometriosis (Ishihara et al, 2003). This effect has been recently confirmed in women with endometriosis by Kim et al (2009). It has also been shown that GnRHa do not significantly influence the extent of decidualization of endometrial stromal cells derived from fertile women during the implantation window; furthermore, they seem to have no adverse effect on human blastocyst invasion (Klemmt et al, 2009). In addition, GnRHa can suppress the expression of nitric oxide synthases and, as a consequence, the generation of peroxynitrite in women with adenomyosis.…”
Section: Medical and Combined Medico-surgical Treatmentmentioning
confidence: 90%
“…Currently, conventional medical therapy plays a role only in treating endometriosis-associated infertility in assisted reproductive technology (ART); it was demonstrated that pretreatment with GnRH agonist for 3–6 months before initiation of in vitro fertilization (IVF) or intracytoplasmic sperm injection could improve the pregnancy rate 4-fold [16]. It has been suggested that long-term use of GnRH agonists could improve endometrial receptivity by reducing aromatase and cyclooxygenase (COX)-2 expression in a eutopic endometrium [17]. Using cryopreserved embryo transfer instead of fresh embryos further improves IVF outcomes by circumventing the excessive ovarian suppression caused by long-term GnRH agonist treatment [18,19].…”
Section: Introductionmentioning
confidence: 99%